Quadro editorial (Estudos em Design, 2023)
EditoresCristina PortugalRita CoutoAvaliadores desta edição v. 31, n. 3 (2023)Adriana GralowAdriana MirandaAlexandre FarbiarzAlexandre OliveiraAline SaviÁlvaro SousaAna BerwangerAna PazminoAndré Ribeiro de OliveiraBeany MonteiroCassia Carrara DomicianoCayley GuimaraesCláudia ZacarClice Mazzilli Cristiane Aun BertoldiChrystianne IvanóskiDaniel Grizante de AndradeDaniel Lacerda RodriguesDaniel LorençoDaniel RaposoDebora Buonano Deborah ChristoDoris KosminskyEva Rolim MirandaEverton da SilvaFernando FoglianoFrederico BraidaGabriel Patrocinio Ione BentzKando FukushimaKátia Carvalhaes PêgoMadalena GrimaldiLaura MartinsLuiz AgnerLuiza Falcão Soares CunhaLuiza NovaesMaíra WoloszynMatheus CezarottoMarcelo ForcatoMarcio GuimarãesMaria Do Carmo Gonçalves CurtisMaria Teresa LopesMarina KunstMariano Lopes de Andrade Neto Nelson KuwaharaRanielder de FreitasRavi PassosRenata CadenaRenata WanderleySandra Maria SouzaSérgio Luciano da SilvaWagner BandeiraVagner GodóiWalter NetoVagner GodóiVera Damazio